Features of embryonic development of parasitic nematodes of the species Trichuris sylvilagi (Nematoda, Trichuridae) - V. Yevstafieva (Publishing House "Akademperiodyka", 2021)
In the present study we established in vitro the terms and stages of exogenous development of nematodes of the species Trichuris sylvilagi Tiner, 1950 isolated from Lepus europaeus, and the degree of the nematode viability at different temperatures. It was found that the most favorable temperature for embryonic development of parasitic helminths was 30°C, with the formation of 88.67 % of viable eggs with a motile larva in 20 days in laboratory conditions, and a lethality rate of 11.33 % of eggs. With a decrease in temperature to 20°C, the embryogenesis occurred in 32 days. The viability of eggs, cultured at that temperature regime, decreased: 68.0 % of eggs reached larval stage, and 32.0 % of eggs died. At 10°C eggs did not develop. At the 32nd day of cultivation, 27.33 % of eggs remained at the zygote stage, 52.0 % at the stage of blastomere cleavage and formation, and 20.67 % died. Embryogenesis was characterized by metric changes in egg parameters. At optimal temperature the growth and development of eggs was accompanied by an increase in the egg width and plugs with a simultaneous decrease in the length of eggs and plugs, as well as thinning of the shell.